HEDONIC TEST AND CHEMICAL QUALITY OF BOMBOLONI PANDAN LEAF FLOUR ADDITION WITH FILLED PATIN FISH FLOSS AS HIGH PROTEIN SNACK - Demitri, Athira; Eka Nenni Jairani; Harahap, Lutfi Henderlan (Universitas Airlangga, 2025)
Bomboloni donuts, which generally taste sweet, are filled with savory Patin fish floss filling, creating unique and interesting product. This can increase people's interest in trying new products and contribute to food industry innovation. This research aimed to determine the organoleptic tests and chemical quality of bomboloni donuts made from pandan leaf flour filled with Patin fish floss as a high protein snack. The research method used was laboratory experimental with completely randomized design (CRD), with three treatments (F1, F2, F3) and two repetitions. The making of pandan leaf flour bomboloni donuts filled with Patin fish floss and organoleptic tests were carried out at the Food Technology Laboratory Institut Kesehatan Helvetia. Then, chemical test analysis was conducted at the Politeknik Teknologi Kimia Industri Medan Laboratory. Data were analyzed using the Kruskal-Wallis test, then continued with the Duncan test. The results showed that there were differences in color (0.000), odor (0.003), taste (0.029), and texture (0.009) from the three formulations of bomboloni donuts made from pandan leaf flour filled with Patin fish floss. Based on the results of Duncan test, the best formulation was obtained in F1, as indicated by the panelists' average preferences for color (3.98), odor (3.70), taste (3.28), and texture (3.43). The chemical test results of the best formulation revealed the following contents: water (24.81%), ash (1.57%), fat (13.54%), protein (12.52%), and carbohydrates (68.83%). The conclusion is that F1 is recommended as a high-protein snack for toddlers to help prevent stunting.